Microtentacle Actuators: Microtentacle Actuators Based on Shape Memory Alloy Smart Soft Composite (Adv. Funct. Mater. 34/2020). (19th August 2020) - Lee, Hyun‐Taek; Seichepine, Florent; Yang, Guang‐Zhong
Abstract : In article number 2002510, Guang‐Zhong Yang, Hyun‐Taek Lee, and Florent Seichepine present micro‐tentacle actuators using a smart soft composite based on a shape memory alloy. A fabrication scheme for miniaturized actuators is proposed by utilizing two‐photon polymerization. The morphing modes are varied by changing the direction of the scaffold lamination and the actuation is controlled via local resistive heating of carbon nanotubes deposited inside of the actuators.